9xa is the common factor.
You can complete the statement by dividing the two terms of the expression of the left side by 9xa, and you will get:
36x^3a + 45xa^2 = 9xa ( 4x^2 + 5a)
The rope is 1 and 1/3 long,1 is the same as saying 3/3,
this means that the rope is 3/3 + 1/3 long,so it is 4/3 foot long,
you now want to get half of this number so that each person has an equal length of rope,so multiply the length of rope by a half,
4/3 x 1/2 = 4/6 , which if simplified = 2/3, this means that each friend gets 2/3 foot of rope.
You can draw this in a diagram by drawing the 1 foot of rope, and then dividing it up into 3 sections. Then add the 1/3 foot of rope into the drawing. It should then be easy to see that altogether there are 4 separate sections of rope and that if each friend has two sections then they will be sharing equal amounts, so consequently each friend has two of the thirds of rope, 2/3
Answer:
x²+ x = 0
x ( x +1 ) = 0
x = -1
x³-25x=0
x ( x² - 25 ) = 0
x² = 25
x = 5
x²=4x
x² - 4x = 0
x ( x- 4 ) = 0
x = 4
4x²-4x=1
4x²-4x - 1 = 0
4 x² - 2x - 2x - 1 = 0
2x ( 2x - 1 ) - 1 ( 2x- 1 ) = 0
2x- 1 ) ² = 0
2x = 1
x = 1/ 2
mark me as brainliest
Answer:
y=2
Step-by-step explanation:
7y-1=13
+1 +1
7y=14
/7 /7
y=2